1981
DOI: 10.1085/jgp.78.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Taste transduction mechanism: similar effects of various modifications of gustatory receptors on neural responses to chemical and electrical stimulation in the frog.

Abstract: Responses in the frog glossopharyngeal nerve inducd by electrical stimulation of the tongue were compared with those induced by chemical stimuli under various conditions. (a) Anodal stimulation induced much larger responses than cathodal stimulation, and anodal stimulation of the tongue adapted to 5 mM MgCI2 produced much larger responses than stimulation with the tongue adapted to 10 mM NaCI at equal current intensities, as chemical stimulation with MgCI2 produced much larger responses than stimulation with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Hence, direct effects of an anodal current on the taste cell could result in neural activation, as the synaptic area would be depolarized. This hypothetical situation is very similar to that proposed by Kashiwayanagi et al (1981), i .e., that anodal current depolarizes the synaptic area of the taste cell, although they do not propose that the apical region becomes hyperpolarized. It would be of interest to obtain intracellular recordings from taste cells under electrical stimulation .…”
Section: Other Proposed Electric Taste Mechanismssupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, direct effects of an anodal current on the taste cell could result in neural activation, as the synaptic area would be depolarized. This hypothetical situation is very similar to that proposed by Kashiwayanagi et al (1981), i .e., that anodal current depolarizes the synaptic area of the taste cell, although they do not propose that the apical region becomes hyperpolarized. It would be of interest to obtain intracellular recordings from taste cells under electrical stimulation .…”
Section: Other Proposed Electric Taste Mechanismssupporting
confidence: 88%
“…Recently, two more suggestions have been made concerning electric taste. Kashiwayanagi et al (1981) and Kobatake and Kamo (1973) have proposed a mechanism for electric taste based on their proposed transduction scheme for taste responses to sapid stimuli in the frog. Sapid stimuli are proposed to induce phase boundary potentials at the taste cell microvillus membrane, which in turn induces current flow through the taste cell synaptic area, resulting in the activation of the afferent nerves .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, when the bitterness of clarithromycin powder suspensions was compared with that of a commercial clarithromycin dry syrup product that is taste masked with polymer (Clarith dry syrup), it was shown that, on the basis of both human gustatory sensation tests and taste-sensor data, almost 99% taste masking (expressed in terms of equivalent quinine concentrations) was achieved for the clarithromycin dry syrup product. The mechanism of bitterness perception via taste receptors has been the subject of much recent discussion (Keast & Breslin 2002b;Nelson et al 2002), and several studies have shown that the action potential and Ca 2 ‡ levels in the taste cells play an important role in the perception of bitterness (Kashiwayanagi et al 1981;Kumazawa et al 1986). Recently, the cloning of a mammalian bitterness receptor has also been reported (Chandrashekar et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to another mechanism, adsorption of chemical stimuli on the microvilli membrane induces the surface potential changes as well as the ion permeability changes at the microvilli membranes, which causes depolarization at the membrane (Kamo et al ., 1974 ; Kurihara et al ., 1978) . The depolarization induces electric current from the microvilli to the cell membranes below the tight junction and depolarizes the synaptic area of the cells (Kashiwayanagi et al ., 1981) . (0.002 mM) or the Ca-channel blockers are present in the solution .…”
Section: )mentioning
confidence: 99%